Preliminary Design Of Paraxylene Plant Using Selective Toluene Disproportionation Process Capacity Of 400,000 Ton/ Year - Mutiara, Delta, Dr. Ir. Ahmad M Fuad, M.T, Ir. Herry Purnama, M.T., Ph.D (2017)
Paraxylene or 1.4 dimethyl benzene is classified into aromatic compounds. Paraxylene is primarily used as raw material in manufacture of terephthalic acid (TPA) and dimethyl terephthalate (DMT). To meet domestic demand, paraxylene plant is designed with production capacity of 400,000 tons/year. 695,205 tons/year of toluenea and 1,214 tons/year of hydrogen are used as raw material. The plant is planned to establish in Cilegon industrial area, Banten in 2020 with land area 3,800 m2 and hire 166 employees. The manufacturing of paraxylene through three stages. At raw materials preparation stage, toluene in liquid phase is vaporized in vaporizer. Pressure of toluene and hydrogen gas is increased into 30 atm . Its temperature is also increased into 450°C in furnace. At process stage, 2 moles of toluene are isomerized to 1 mole xylene and 1 mole benzene by catalyst ZSM-5 and hydrogen as support material. The reaction takes place in reactor fixed bed multitube non isothermal adiabatic. At purification product stage, hydrogen, benzene and toluene are separated by separator and distillation process. Paraxylene is separated from xylene by crystallization process to obtain paraxylene crystal of 99% wt. Paraxylene crystall is melted in melter and ready to be marketed. Supporting unit of the plant consist of water supply as much as 968,907 kg/hour which are processed from Ciujung River, provision 296,130,095 kJ/hour of saturated steam, provision 998 kW of electricity, provision 236 liters/hour of diesel fuel, provision 50 m3/hour of instrumentation air and provision 3,252 kg/hour of ammonia. Amount of working capital is Rp.162,007,798,698. The economic analysis shows that percent return on investment (ROI) before tax is 86% and after tax is 64%. Pay out time (POT) before tax is 1 year and pay out time (POT) after tax is 1.3 year. Break even point (BEP) at 43.54 % capacity, Shut down point (SDP) is amounted at 27% capacity, and Discounted cash flow (DCF) is 25%. From data results of feasibility analysis can be concluded that the plant is profitable and feasible to be established.